Human radiation dosimetry of 6-[(18)F]FDG predicted from preclinical studies - Muzic, Raymond F. (American Association of Physicists in Medicine, 2014)
Purpose: The authors are developing 6-[(18)F]fluoro-6-deoxy-D-glucose (6-[(18)F]FDG) as an in vivo tracer of glucose transport. While 6-[(18)F]FDG has the same radionuclide half-life as 2-[(18)F]fluoro-2-deoxy-D-glucose (2-[(18)F]FDG) which is ubiquitously used for PET imaging, 6-[(18)F]FDG has special biologic properties and different biodistributions that make it preferable to 2-[(18)F]FDG for assessing glucose transport. In preparation for 6-[(18)F]FDG use in human PET scanning, the authors would like to determine the amount of 6-[(18)F]FDG to inject while maintaining radiation doses in a safe range. Methods: Rats were injected with 6-[(18)F]FDG, euthanized at specified times, and tissues were collected and assayed for activity content. For each tissue sample, the percent of injected dose per gram was calculated and extrapolated to that for humans in order to construct predicted time-courses. Residence times were calculated as areas under the curves and were used as inputs to OLINDA/EXM in order to calculate the radiation doses. Results: Unlike with 2-[(18)F]FDG for which the urinary bladder wall receives the highest absorbed dose due to urinary excretion, with 6-[(18)F]FDG there is little urinary excretion and osteogenic cells and the liver are predicted to receive the highest absorbed doses: 0.027 mGy/MBq (0.100 rad/mCi) and 0.018 mGy/MBq (0.066 rad/mCi), respectively. Also, the effective dose from 6-[(18)F]FDG, i.e., 0.013 mSv/MBq (0.046 rem/mCi), is predicted to be approximately 30% lower than that from 2-[(18)F]FDG. Conclusions: 6-[(18)F]FDG will be safe for use in the PET scanning of humans.